Effects of flexible ureteroscopy on renal blood flow: a prospective evaluation - ÖZDEMİR, BURCU; ŞENER, TARIK EMRE; TANIDIR, YILÖREN (TAYLOR & FRANCIS LTD, 2018)
Objective: This study aimed to investigate the effects of flexible ureteroscopy (F-URS) on renal blood flow using renal Doppler ultrasound (US). Materials and method: Patients undergoing F-URS were scheduled for Doppler US preoperatively and postoperatively. Peak systolic velocity (PSV), end-diastolic velocity (EDV), resistive index (RI) and pulsatility index (PI) were reported. Technical details, operation time, stone characteristics and complications were recorded. Patients were grouped as 9.5/11.5-Flex-X2, 10/12-Flex-X2, 10/12-Flex-XC, 12/14-Flex-X2 and 12/14-Flex-XC, with 28, six, three, seven and two patients in each group, respectively. Results: Forty-six patients with a mean age of 41.24 years and stone volume of 1685 mm(3) were enrolled. The PSV, EDV, PI and RI of renal arteries in all groups in preoperative and postoperative periods were similar. Arcuate artery measurements in all groups were also similar in preoperative and postoperative periods, without any significant difference except in two parameters: RI in the 9.5/11.5-Flex-X2 group and PSV in the 12/14-Flex-X2 group. The resistive index in the arcuate artery of the 9.5/11.5-Flex-X2 group was increased from 0.59 to 0.62 cm/sec postoperatively. The PSV in the arcuate artery of the 12/14-Flex-X2 group was decreased from 30.9 to 27.2cm/sec. Three patients had urinary tract infections postoperatively and two had sepsis. Conclusion: This study suggests that compatible ureteroscope-ureteral access sheath combinations with a lumen difference of more than 1.5 Fr can provide safe outcomes in terms of renal blood flow. F-URS can safely be performed in terms of renal perfusion and complication rates with appropriate equipment and instruments.
Keywords: Renal blood flow; ultrasonography; ureteroscopy; URETERAL ACCESS SHEATH; DOPPLER ULTRASOUND; FUNCTIONAL RESERVE; IRRIGATION FLOW; LASER; STONES